ANALISIS DAMPAK (I‘TIBĀR AL-MA’ĀL): TEORI YANG TERPINGGIRKAN DALAM WACANA USUL FIKIH DI INDONESIA - Adib, Muhammad (MAQASHID, 2024)
This research examines the impact analysis (i‘tibār al-ma’āl) as a marginalized theory in the discourse of Islamic jurisprudence in Indonesia. The starting point is the gap between the dynamics of Islamic jurisprudence discourse in the Middle East and Indonesia regarding this theory. Through a qualitative approach that relies on library research and content analysis methods for syllabis, SAPs and textbooks used in Islamic universities, Islamic schools, and Islamic boarding schools, this research shows that the impact analysis (i‘tibār al-ma’āl) theory is not part of the curriculum content and learning topics in the Islamic education institutios in Indonesia. This of course has an impact on the very minimal academic interest in Islamic jurisprudence discourse in Indonesia regarding this theory. This research also recommends that this theory has to be added to the curriculum content and learning topics, in order to enrich perspectives on Islamic jurisprudence discourse in Indonesia.